2018
DOI: 10.1111/1755-5922.12480
|View full text |Cite
|
Sign up to set email alerts
|

Statins and risk of cataracts: A systematic review and meta‐analysis of observational studies

Abstract: Summary Introduction Two previous meta‐analyses evaluated the risk of cataracts associated with statins, but did not include relevant studies suggesting a cataractogenic effect. Aims The aim of this systematic review and meta‐analysis of observational studies is to evaluate such association considering the latest published evidence. Methods A literature search was conducted to identify observational, comparative studies evaluating the risk of developing cataracts in patients treated with statins. A meta‐analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 78 publications
(195 reference statements)
3
9
0
2
Order By: Relevance
“…More important, the analysis performed after exclusion of lovastatin (in order to minimize a notoriety bias due to the fact that lovastatin was the first historically suspected statin and thus reduces attrition of susceptibles) found similar trends, clearly evidencing an increased risk of cataract report with all statins in general. However, the ROR values obtained in the present study were relatively low for disproportionality studies suggesting, in accordance with the recent meta‐analysis , that the magnitude of cataract risk with LLD is low.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More important, the analysis performed after exclusion of lovastatin (in order to minimize a notoriety bias due to the fact that lovastatin was the first historically suspected statin and thus reduces attrition of susceptibles) found similar trends, clearly evidencing an increased risk of cataract report with all statins in general. However, the ROR values obtained in the present study were relatively low for disproportionality studies suggesting, in accordance with the recent meta‐analysis , that the magnitude of cataract risk with LLD is low.…”
Section: Discussionsupporting
confidence: 91%
“…Very recently, a systematic review and meta-analysis including twenty-one studies found an OR value = 1.11 (95% CI 1.02-1.21). The small magnitude of the risk was explained by high betweenstudies heterogeneity [7]. In the present analysis, we found that the four most frequently reported statins in VigiBase â were in descending order: atorvastatin, simvastatin, rosuvastatin and lovastatin and we described a significant ROR value for all statins in general.…”
Section: R E S U L T Ssupporting
confidence: 49%
“…Compared with older antipsychotic drugs (Shahzad et al, ), statins and quetiapine appear to have better safety margins based on biochemical studies of lenses obtained from humans treated with lovastatin and simvastatin where no changes in lens sterol content occurred at approved daily doses (Mitchell & Cenedella, ) and many years of safe human experience (Laties et al, ; Schlienger, Haefeli, Jick, & Meier, ; von Sallmann et al, ). Recent meta‐analysis of statin use shows little if any risk compared with its beneficial effects (Alves, Mendes, & Batel Marques, ; Yu et al, ). The mechanism of cataract formation, the site of inhibition along the cholesterol biosynthetic pathway, and drug lens exposure are necessary pieces of information to establish a clearer safety perspective (de Vries, Vermeer, Bloemendal, & Cohen, ; Mitchell & Cenedella, ).…”
Section: Discussionmentioning
confidence: 99%
“…Впервые о возможном влиянии статинов на риск развития катаракты описано в экспериментальном исследовании на собаках, получавших большие дозы препаратов этого класса [4]. Механизм, благодаря которому статины могут провоцировать развитие катаракты, до сих пор неизвестен, лишь в нескольких работах обсуждаются возможные причины такой взаимосвязи [5][6][7][8]. Результаты доклинических исследований статинов продемонстрировали решающую роль холестерина в целостности мембран и поддержании структуры, прозрачности хрусталика, поэтому прием этих препаратов и, как следствие, снижение холестерина, могут приводить к развитию катаракты [5,9,10].…”
unclassified
“…В 2018г был выполнен систематический обзор и мета-анализ наблюдательных исследований для оценки риска развития катаракты у пациентов, принимающих статины [6]. Работы [2], в которых не обнаружено убедительных доказательств связи между приемом статинов и катарактой, не включали наблюдательные исследования, свидетельствующие о наличии такой ассоциации.…”
unclassified